Analysis of Anemia Among Pregnant Women at The Work Area of Kilasah Health Centre In 2019 - Shinta Novelia; Rukmaini Rukmaini; Pungki Sulistriani (MBUnivPress, 2022)
Anemia is the biggest public health problem in the world especially in the group of women in reproductive age. Globally, the case of anemia among women around the world was41.8%. One of the causes of anemia is pregnancy. Anemia in women enthusiastically can cause fatigue, weak body, reduction of capacity / ability or work productivity. This study aimed to analyze the incidence of anemia among pregnant women in the area of the health center in the Serang City in 2019. This researchdes used Cross Sectional design and a total Sampling technique which consisted of 120 people. The research instrument consisted of questionnaires about polarization, support of family and general habits in the military. The results of this study show that there is a significant relationship between eating patterns with a value of p = 0.010, family support with a value of p = 0.002, and there is no relationship between the drinking tea activity with a value of p = 0.245, to the incidence of anemia in pregnant women. It is expected to provide health education about anemia in pregnant women can be lowered and the need to educate about anemia during pregnancy during the Antenatal Care (ANC) examination.